(untitled) (Jurnal Mekanikal, 2018)
The aim of this study is to help in improving the plant layout of a manufacturing company. The objective is to redesign a new layout in order to improve the productivity. Industrial Engineering techniques will be implemented to identify the entire problem, which occurs in the production floor. After the main problem has been identified, CIMFactory simulation software that includes FactoryCAD and FactoryFLOW will be used to generate result reports. Critical analysis will be done based on the reports and the best alternative layout will be suggested to the company’s management for future development.